Digestibilidade e tempo de retenção dos grãos de sorgo processados durante a ensilagem em equinos - Oliveira, Kátia De [UNESP]; Bittar, Carla Maris Machado; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Soutello, Ricardo Velludo Gomes De [UNESP] (UFBA - Universidade Federal da Bahia, 2014)
The objective was to evaluate apparent digestibility of nutrients and the mean retention time of high-moisture grains of sorghum with low (SLT) and high (SHT) tannin submitted to two processing during ensilage, grinding and rolling. There were used four castrated male horses, crossbred. It was used randomized block by design for four replications, totalizing four repetitions for each treatment. The treatments consisted of SLT e SHT submitted to two processing during ensilage, griding and rolling, in 2 x 2 factorial arrangement tested (2 sorghum genotypes and 2 processing). The daily DM intake was 2% body weight, this way the test-diets were composited by 30% SLT and 70% of hay. There observed differences (P<0.05) between SLT and SHT, as like, of processing method, in that best results were for grinding-SLT, whose means values were to DCDM, DCOM, DCCE, DCCP and DCStarch of 83.82, 83.91, 85.17, 86.56 e 84.72%. Furthermore, not identified significant effect between the grains studied, as well as the processing, on the mean retention time, with an average of 17.5 h. It was concluded that the grinding of grain sorghum silage increases nutrient digestibility. The mean retention time in horses presented similar among grain sorghum silages as rolled and grinded.

Objetivou-se determinar em equinos a digestibilidade dos nutrientes e o tempo médio de retenção dos grãos de sorgo de baixo e alto teores de tanino submetidos na ensilagem a dois processamentos, prensagem e moagem. Foram utilizados quatro cavalos castrados sem raça definida delineados em blocos casualizados, resultando em quatro repetições por tratamento. Os tratamentos consistiram de silagens de grãos úmidos de sorgo de baixo tanino e alto teor de tanino submetidos a dois tipos de processamentos, prensagem e moagem, arranjados em esquema fatorial 2x2 (2 genótipos de sorgo e 2 processamentos na ensilagem). Observaram-se diferenças significativas entre as silagens com baixo e alto teor de tanino, bem como dos processamentos na ensilagem, no qual os melhores resultados obtidos foram para a silagem de grãos úmidos de sorgo de baixo tanino moída, com os valores para CDMS, CDMO, CDEB, CDPB e CDAmido, de 83,82; 83,91; 85,17; 86,56 e 84,72%, respectivamente. Ainda, não se identificou efeito significativo entre os grãos estudados, bem como dos processamentos, sobre o tempo médio de retenção, com média de 17,5h. Concluiu-se que a moagem dos grãos de sorgo na ensilagem aumenta a digestibilidade dos nutrientes. O tempo médio de retenção em equinos apresentou-se similar entre os grãos de sorgo ensilados sob a forma prensada e moída.
Digestibility and retention time of grains of sorghum processed during ensilage in equine
Keywords: cavalo; moagem; prensagem; saco de náilon móvel; tempo médio de retenção; grinding; horse; mean retention time; mobile nylon bag; rolling